2021
DOI: 10.1080/22311866.2021.1987322
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of the Antibiotic Activity by the Essential Oils of Eugenia brasiliensis Lam. and Piper mosenii C. DC.

Abstract: The present study aimed to investigate the antibiotic-enhancing activity of the essential oils obtained from the leaves of Eugenia brasiliensis Lam (EOEb) and Piper mosenii C. DC. (EOPm) against multiresistant strains of Escherichia coli 06 and Staphylococcus aureus 10. The essential oils were obtained by hydrodistillation, and the minimum inhibitory concentrations (MIC) were determined through the broth microdilution method. The EOEb enhanced the activities of norfloxacin and erythromycin against Staphylococc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…[169][170][171] Additionally, frequent studies have shown that the leaves' essential oils have antibacterial activity. 32,[172][173][174] On the other side, growing evidence indicates that the fruit's versatile bioactive composition, mostly its anthocyanin and ellagitannin contents, is associated antiinflammatory activities in vitro. Grumixama's chemical attributes, sometimes unique to most fruits, hold a great potential to be used against non-communicable diseases in vivo.…”
Section: Food and Function Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…[169][170][171] Additionally, frequent studies have shown that the leaves' essential oils have antibacterial activity. 32,[172][173][174] On the other side, growing evidence indicates that the fruit's versatile bioactive composition, mostly its anthocyanin and ellagitannin contents, is associated antiinflammatory activities in vitro. Grumixama's chemical attributes, sometimes unique to most fruits, hold a great potential to be used against non-communicable diseases in vivo.…”
Section: Food and Function Reviewmentioning
confidence: 99%
“…No specific compound quantification has been conducted in yellow grumixama, but given its total carotenoid content, 142 it can be supposed that at least a few of the fruit's carotenoids would be classified as high or very high. On the other side, according to the chromatogram identification of Silva et al , 32 dark-colored grumixama can be classified as having low to moderate levels of specific carotenoids.…”
Section: Atlantic Forest Berriesmentioning
confidence: 99%
See 1 more Smart Citation